THE IMPORTANCE AND TASKS OF THE EFFICIENCY ANALYSIS OF THE ACTIVITY OF THE COMMERCIAL ORGANIZATION IN THE FINANCIAL MARKETS WITHIN CONTEMPORARY BUSINESS ANALYSIS - P. Kukushkin (Вестник университета)
In the Russian practice there is no technique of the analysis of efficiency of activity of the companies using receptions of the modern business analysis. Creation of a similar technique is impossible without allocation of specific objectives of the analysis of efficiency of activity of the organizations in the financial markets. The purpose of this work consists in the description of a technique of statement of tasks of the analysis of efficiency as element of the economic analysis. Need of implementation of the analysis of activity of the organization in the financial markets within stakeholders approach is proved in the article, definition of efficiency is given. Statement of tasks within the business analysis is equated to requirements of key interested parties. The tasks of the analysis of efficiency put as a result of a research allow to give the objective characteristic of activity of the company from a position of primary groups of stakeholders.